Controlling neuroinflammation in the retina through A2AR modulation: potential therapeutic implication in glaucoma - Madeira, Maria Helena Bica (2016)
Tese de doutoramento em Ciências da Saúde, na especialidade de Ciências Biomédicas apresentada à Faculdade de Medicina da Universidade de Coimbra